Practitioner-centred research on academic development of higher education in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
Endowed with one of the most dynamic and competitive economies in Southeast Asia, Malaysia is gradually differentiating and improving the quality of its higher education. The practitioner-centred research (PCR) is one of the initiatives aimed at generating successful professional practices in the field of academic development. PCR is a research method that can be conducted to influence professional practices. Unlike other traditional or theoretical research methods, PCR provides an immediate impact to a practitioner’s action plan, especially when practitioners themselves undertake research activities.